The Use Of Information Technology In Madrasah Archival Administration - Junita Putri; Iqbal Amar Muzaki; Wahidin Wahidin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The integration of information technology in madrasah institutions has brought new challenges, especially for administrative staff who lack the digital literacy necessary to operate these systems effectively. This technological gap hinders their ability to adapt to modern advances, resulting in operational inefficiencies. In the context of records management, it is essential for staff to optimize technology to facilitate document access and retrieval. This article aims to explore the use of information technology in school archiving systems and highlight its positive impact on madrasah institutions. Using a descriptive qualitative approach through a literature review, data were collected by systematically analyzing relevant books, journals, and academic articles. The findings show that the implementation of adaptive information technology in archive administration significantly improves school management. This transition is vital for the continuous improvement and future development of madrasah institutions. Ultimately, this study serves as a comprehensive reference for optimizing information technology in archive administration.